Comparative study of methods to aflatoxin M1 determination - Maria de Sylos, Célia (1996)
Various trials were carried out to choose the extracting solvent and the best technique for removing interfering substances from samples of rnilk for the TLC detennination of aflatoxin Mj. For extraction acetone, methanol and chloroform were utilized either singly, in combination with each other or with water. Precipitation with heavy metal salts, partition between immiscible solvents and conventional column chromatography were evaluated for clean-up. Heavy metals by themselves were not effective in eliminating interfering substances. The combined use of chloroform and a chromatographic colurnn proved to be the most efficient procedure for extraction and c1ean-up. Colurnns packed with silica or silica-Cj8 gave better results than that of cellulose. HPLC with solid phase extraction, c1ean-up in silica gel column and trifluoroacetic acid derivatization and fluorescence detection presented much higher sensitivity and specificity than TLC with visual quantification based on fluorescence intensity.